FACTORS AND DETERMINANTS OF HIGH BLOOD PRESSURE AMONG AGE GROUPS IN MOSUL - Abdalrahim H. Eefan (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Hypertension is a major global health problem characterized by increased arterial pressure resulting from multiple behavioral, physiological, and pathological factors. Specific Background: In Mosul, limited recent epidemiological data exist, particularly among younger populations under 50 years of age diagnosed with hypertension. Knowledge Gap: There is insufficient localized evidence regarding dominant determinants and patient behavior related to hypertension management in this age group. Aims: This study aimed to estimate the prevalence of hypertension among individuals under 50 in Mosul and to identify its main causes and management approaches. Results: Among 250 patients, hypertension was most prevalent in the 30–40 age group (49%). The leading determinants were psychological stress and difficult economic conditions, followed by kidney disease, obesity, smoking, and family history. Lifestyle modifications primarily included dietary changes (40%) and physical activity (30%), while treatment adherence varied, with only 52% taking medication regularly. Novelty: This study highlights the dominant role of socioeconomic hardship and psychological stress as primary contributors to hypertension in a younger population. Implications: These findings emphasize the need for targeted public health strategies addressing social conditions, stress management, and improved treatment adherence to control hypertension in similar populations. Highlights• Psychological burden and financial constraints emerge as dominant determinants• Highest proportion observed in individuals aged 30–40 years• Medication adherence remains inconsistent among diagnosed patients KeywordsHypertension; Psychological Stress; Socioeconomic Status; Young Adults; Lifestyle Modification